Redesign Fondasi Bore pile Menjadi Tiang Pancang dengan Variasi Diameter Berdasarkan Analisis Daya Dukung dan Penurunan pada Gedung Pendidikan di Kota Jambi - Tiara Nanda; Dila Oktarise Dwina; Nita Astasya (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The planned bore pile foundation for an educational building in Jambi City faced construction challenges due to compacted sandy soil conditions and the influence of a relatively high-water table, necessitating a more suitable foundation alternative. This study aims to redesign the bore pile foundation into a driven pile foundation and analyze the effect of diameter variations on bearing capacity and foundation settlement to determine the optimal diameter. The study utilized soil investigation data in the form of Standard Penetration Tests (SPT) and Cone Penetration Tests (CPT/Sondir), as well as building structure loading data. The analysis was conducted on spun pile foundations with diameters of 0.4 m, 0.5 m, and 0.6 m at depths of 14 m and 16 m. Bearing capacity was calculated using the Meyerhof method based on SPT data and compared with the results of the ALLPile program analysis, while foundation settlement was analyzed using the Vesic method and ALLPile method. The research results show that bearing capacity increases with increasing pile diameter and depth, while settlement values tend to decrease. A comparison between the Meyerhof and ALLPile methods shows relatively consistent results with no significant differences. All foundation variations meet the bearing capacity and allowable settlement requirements. Based on an evaluation of bearing capacity, settlement, and design efficiency, piles with a diameter of 0.5 m and a depth of 14 m were selected as the most optimal foundation alternative for the soil conditions at the study site.